2021
DOI: 10.1111/1440-1681.13476
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone chemosensitizes human colorectal cancer cells to imatinib via uptake/efflux genes modulation

Abstract: Imatinib (IM) is a pharmaceutical drug that inhibits tyrosine kinase enzymes that are responsible for the activation of many proteins by signal transduction cascades as c‐Abl, c‐Kit and the platelet‐derived growth factor (PDGF) receptor. Thymoquinone (TQ) is an active constituent of Nigella sativa seeds. Thymoquinone benefits are attributed to its medicinal uses as antioxidant, anticancer and antimicrobial agent. This study aimed to investigate the impact of using TQ with IM in the HCT116 human colorectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Resistance to IM was reported to develop in cancer patients through several mechanisms including the modulation of the expression of drug efflux and influx transporters[ 101 , 102 ]. In a study conducted by Thabet et al [ 103 ], TQ was found to improve the anti-proliferative and apoptotic effects of IM in colorectal cancer cells in vitro . Interestingly, this was accompanied by a significant decrease in the expression of the drug transporters ATP-binding cassette (ABC) subfamily B member (ABCB) 1, ABCG2 and human organic cation transporter 1 leading to a significant increase in IM uptake /efflux ratio compared to IM alone.…”
Section: Tq Effects Against Cancer Cellsmentioning
confidence: 99%
“…Resistance to IM was reported to develop in cancer patients through several mechanisms including the modulation of the expression of drug efflux and influx transporters[ 101 , 102 ]. In a study conducted by Thabet et al [ 103 ], TQ was found to improve the anti-proliferative and apoptotic effects of IM in colorectal cancer cells in vitro . Interestingly, this was accompanied by a significant decrease in the expression of the drug transporters ATP-binding cassette (ABC) subfamily B member (ABCB) 1, ABCG2 and human organic cation transporter 1 leading to a significant increase in IM uptake /efflux ratio compared to IM alone.…”
Section: Tq Effects Against Cancer Cellsmentioning
confidence: 99%
“…This combination demonstrated a significant suppressive effect at 5-FU concentrations of 0.027 and 0.055 mM, suggesting that TQ could potentially amplify the growth-suppressive effects of 5-FU on cancer cells [ 127 ]. The concurrent administration of 30 μM imatinib, a tyrosine kinase inhibitor, and 10 μM TQ resulted in the suppression of ABCB1, ABCG2, and hOCT1, thereby enhancing the uptake of imatinib in HCT-116 cells [ 128 ]. The combination of 20 and 40 µM TQ with 0.2 µM cisplatin amplified the cytotoxicity of cisplatin in HCT-116 and COLO205 cells.…”
Section: Tq and Colorectal Cancermentioning
confidence: 99%
“…Thymoquinone has been employed in treatment of various cancers such as lung tumor, breast tumor and colorectal tumor, among others. Thymoquinone can affect various signaling networks in cancer therapy that PI3K/Akt signaling is among them and it can be used as a chemo‐sensitizer agent (Alam et al 2022; Karim et al 2022; Thabet et al 2021; Abd‐Rabou et al 2021). A recent experiment has employed docetaxel and thymoquinone in treatment of prostate cancer.…”
Section: Pi3k/akt In Therapy Resistancementioning
confidence: 99%